Kiedy znikną białe plamy. Spojrzenie na współczesną historiografię Polski - Kenney, Padraic; Madej, Anna (Pamięć i Sprawiedliwość, 2008)
The author reviews trends in Modern Polish History among Polish and Anglo-American scholars. In the study of the 19th century and the Second Republic, he fi nds increasing attention to the ways that national identity is invented, and in particular to the importance of relations with other national groups shaped Poles’ conceptions of themselves. Scholarship on World War Two, as well, is now recognizing that confl ict’s role as a crucible of national identity, though some historians still limit themselves to simpler stories of national unity and betrayal. The Communist period, in turn, is yielding some of the most innovative work, as scholars move from fi lling in the blank spots to investigating the mechanisms of accommodation and opposition. In conclusion, the author offers some thoughts on the directions that Polish history can take in the near future.